2016
DOI: 10.1509/jm.15.0415
|View full text |Cite
|
Sign up to set email alerts
|

A Thematic Exploration of Digital, Social Media, and Mobile Marketing: Research Evolution from 2000 to 2015 and an Agenda for Future Inquiry

Abstract: Over the past 15 years, digital media platforms have revolutionized marketing, offering new ways to reach, inform, engage, sell to, learn about, and provide service to customers. As a means of taking stock of academic work's ability to contribute to this revolution, this article tracks the changes in scholarly researchers’ perspectives on three major digital, social media, and mobile (DSMM) marketing themes from 2000 to 2015. The authors first use keyword counts from the premier general marketing journals to g… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

4
498
0
27

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 764 publications
(581 citation statements)
references
References 131 publications
4
498
0
27
Order By: Relevance
“…Nevertheless, despite the rapidly growing number of published articles, the current literature still lacks of some answers. Academics noted that future studies should highlight social media strategy and its key elements, but also the balance between both online and offline marketing approaches (Pomirleanu & Schibrowsky, 2013;Lamberton & Stephen, 2016). This justifies the assumption, that social media marketing research will continually grow and develop in future (Ngai, 2003).…”
mentioning
confidence: 94%
See 1 more Smart Citation
“…Nevertheless, despite the rapidly growing number of published articles, the current literature still lacks of some answers. Academics noted that future studies should highlight social media strategy and its key elements, but also the balance between both online and offline marketing approaches (Pomirleanu & Schibrowsky, 2013;Lamberton & Stephen, 2016). This justifies the assumption, that social media marketing research will continually grow and develop in future (Ngai, 2003).…”
mentioning
confidence: 94%
“…As noted by Lamberton & Stephen (2016), the transformation in the subject has paralleled various technological innovations (for example high-speed broadband and mobile devices); as a result, it penetrated the directions of the academic interest in the last years. The academic literature appears to prove that; only in the last 20 years it grew in the enormous number of publications.…”
mentioning
confidence: 99%
“…Essa evolução foi possível graças ao surgimento da Internet como mídia, que modificou a forma como as empresas se conectam com seus consumidores (Hoffman & Novak, 1996) e abriu espaço para novos comportamentos, baseados em interações e experiências (Lamberton & Stephen, 2016). Uma implicação teórica desse movimento é o questionamento acerca do futuro da propaganda tradicional (Kumar & Gupta, 2016;Schultz, 2016), uma vez que as empresas devem lidar com um público-alvo cada vez mais disperso, organizado em pequenas comunidades nas redes sociais virtuais.…”
Section: Introductionunclassified
“…Analysis of five leading scientific marketing journals for the period 2000-2015 revealed that in 160 analyzed articles actually three areas were most frequently covered: digital, social media and mobile marketing (DSMM). In these articles, three directions of DSMM technology influence were most frequently analyzed: a) on consumer self-expression and communication; b) on decision-making process as a powerful tool; c) on market intelligence as an increasing source of confident data [24].…”
Section: Introductionmentioning
confidence: 99%